Photo-immobilized EGF chemical gradients differentially impact breast cancer cell invasion and drug response in defined 3D hydrogels. (September 2018) - Fisher, Stephanie A.; Tam, Roger Y.; Fokina, Ana; Mahmoodi, M. Mohsen; Distefano, Mark D.; Shoichet, Molly S.
Abstract: Breast cancer cell invasion is influenced by growth factor concentration gradients in the tumor microenvironment. However, studying the influence of growth factor gradients on breast cancer cell invasion is challenging due to both the complexities of in vivo models and the difficulties in recapitulating the tumor microenvironment with defined gradients using in vitro models. A defined hyaluronic acid (HA)-based hydrogel crosslinked with matrix metalloproteinase (MMP) cleavable peptides and modified with multiphoton labile nitrodibenzofuran (NDBF) was synthesized to photochemically immobilize epidermal growth factor (EGF) gradients. We demonstrate that EGF gradients can differentially influence breast cancer cell invasion and drug response in cell lines with different EGF receptor (EGFR) expression levels. Photopatterned EGF gradients increase the invasion of moderate EGFR expressing MDA-MB-231 cells, reduce invasion of high EGFR expressing MDA-MB-468 cells, and have no effect on invasion of low EGFR-expressing MCF-7 cells. We evaluate MDA-MB-231 and MDA-MB-468 cell response to the clinically tested EGFR inhibitor, cetuximab. Interestingly, the cellular response to cetuximab is completely different on the EGF gradient hydrogels: cetuximab decreases MDA-MB-231 cell invasion but increases MDA-MB-468 cell invasion and cell number, thus demonstrating the importance of including cell-microenvironment interactions when evaluating drug targets.